A nova reforma penal na modernidade tardia brasileira: uma análise das tendências político-criminais por trás da Lei 13.964/2019. - Oliveira, Fábio Aragone Andrade de (2024)
The research object of study is the relationship between the new brazilian penal reform (Law 13.964/2019) and late modernity, with an emphasis on the analysis of the political-criminal trends behind its advent. In general terms, the objective is to examine the context underlying the consolidation of the aforementioned legal diploma, investigating the extent to which the control strategies brought within it mirror structural trends common to other late-modern western democracies in late modernity, without ignoring the latent interests in the light of which they were guided. It is based on the hypothesis that the production and application of brazilian punitive norms reflect a globalizing trend in late-modern western penal culture, which is not limited to the mere transplantation of legislation between countries, but reveals itself to be associated with a set of transformations experienced by western democracies in late modernity, whose sociocultural approach was driven by the globalizing process, which directly impacted the experiences, metamorphoses and habits that gave a new aspect to the relationship between society and crime. For the development of the research, a deductive analysis of qualitative data collected from methodological triangulation is proposed, combining different sources and collection methods, namely bibliographic review, document analysis, audiovisual observation and elite interviewing. Thereby, we seek not only to understand the dominant values, priorities and objectives within the scope of late-modern punitive policies, but also to timeless and universal dogmas, as well as the linearity with which normative vicissitudes are usually portrayed, presenting a critical interpretation of the brazilian criminal justice system on the margins of utopias or radical constructivisms.